A política de regularização fundiária de assentamentos rurais executada nos termos da Lei nº 13.465/2017 como forma de consolidar os descaminhos da reforma agrária - Dias, Carla Fernanda Rodrigues (2022)
The realization of the socio-economic objectives and goals of the agrarian reform was reduced to insignificance with Law No. 13.465/17, which, among other issues, aims at the emancipation of old settlements that have been created for 15 years until the promulgation of the aforementioned law, which will be consolidated and emancipated through the execution of the Land Regularization Policy through the Land Registry and Land Regularization Program and following up with the successor Program Titula Brasil. This new program aims at the regularization and negotiation of titles to the tracts of land held by the settlers, to be delivered against payment in order to become the private owners of such lands. In this sense, the study seeks to analyze the current scenario of agrarian reform in order to demonstrate the structural difficulties to be faced by settlers; analyze the (in)effectiveness of the agrarian reform implemented under the support public policies developed and transformed with the support of the democratic model built in the country's legal system. Then, the analysis will be developed based on the objectives and goals set forth in the National Plans for Agrarian Reform - NPAR as opposed to some public policies to support agrarian reform developed through federal programs responsible for attempts to achieve the objectives and goals set forth in the body of NPAR. Criticisms were also built based on the theories of southern epistemologies, ecology of knowledge, post-abyssal thinking and the sovereignty of society in democratic systems that have characteristics of totalitarian regimes in order to demonstrate the findings regarding the (in)sufficiency of the socioeconomic conditions of the settlers to emancipate themselves, conditions arising from the (mis)paths of public policies to support agrarian reform studied and used as a sample in this research. As hypotheses, it is possible to visualize the capacity to finish the agrarian reform and still privatize all the conditions of access to land or insufficiency and increase in the difficulty of access to the policies responsible for making the settlers' socioeconomic development viable. Both results will put pressure on settlers and result in vulnerability and exposure to financial speculators, increasing the number of parcel sales, which will intensify the process of reconcentration of land in the country, especially because settlers would not obtain the necessary public support for the effective achievement of the objectives of agrarian reform.